Different methods of bacterial inoculation on the yield of chamomile blossoms and essential oil - A. Mostafa; M. Khalafallah; S. AboSedera; H. Fathy; A. Higazy (Global Journal of Environmental Science and Management)
Chamomile is one of the most wide spread medicinal plant cultivated in Egypt. This work aimed at enhancement of blossoms and oil production of chamomile plants via biofertilization with PGPRs under organic farming system. In this study, 6 bacterial strains were applied using two different inoculation techniques. The first application method was throughout soaking the roots of seedlings in the bacterial suspension before transplanting. The second technique was by adding the bacterial inocula to soil 2 weeks after transplantation. The results showed that root dipping method displayed high impact on the yield of chamomile blossoms and essential oil percentage. Furthermore, the soil application of the bacterial inocula didn’t show any significant impact in this respect. Where Paenibacillus polymyxa, Bacillus subtilis, Serratia plymuthica and Streptomyces subrutilus increased the dry weight of chamomile blossoms compared to the control, essential oil content increased significantly in case of Serratia plymuthica, Stenotrophomonas rhizophyla and Bacillus subtilis. The current results also indicated that bacterial strains produced the highest indole-3-acetic acid and gibberellic acid resulted in the highest yield of both flowers and essential oil.